Cervical Ripening Using Foley Balloon with or without Oxytocin: A Systematic Review and Meta-Analysis - Gallagher, Lauren T.; Gardner, Benjamin; Rahman, Mahbubur; Schoen, Corina; Connolly, Katherine A.; Hankins, Gary D.; Saade, George R.; Saad, Antonio F. (American Journal of Perinatology, 2019)
Objective To assess available evidence regarding the use of oxytocin in conjunction with Foley balloon (FB) for cervical ripening.Methods Databases from MEDLINE (U.S. National Library of Medicine, 1980—May 12, 2017), MEDLINE (Ovid, 1980—June 30, 2017), the Cochrane Library Controlled Trials Register, ClinicalTrials.gov, and Web of Science were queried for studies on FB cervical ripening with or without oxytocin in pregnant women. Search terms included: “balloon dilatation” OR “mechanical methods” OR “mechanical method” OR “mechanical dilation” OR “mechanical dilatation” OR “mechanical dilations” OR “mechanical dilatations” OR “balloon” OR “Foley” AND “Pitocin” OR “oxytocin.” All relevant references were reviewed. Literature for inclusion and methodological quality were reviewed based on the Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines.Results Out of 344 citations, six randomized clinical trials (1,133 patients) fulfilled our inclusion criteria. The pooled estimate showed that the cesarean delivery (CD) rate did not differ (relative risk [RR]: 0.91 (95% confidence interval [CI] [0.76–1.10]; p = 0.23) between patients who underwent preinduction cervical ripening with FB alone versus those who received oxytocin in addition to FB. Heterogeneity was not significant among studies (I2 0.0%; p = 0.64). Furthermore, no differences in other outcomes such as composite and maternal outcomes were detected between these two groups. Compared with simultaneous use of oxytocin with FB, the Foley alone cervical ripening group had a longer induction to delivery time, and lower deliveries within 12 and 24 hours. Subgroup analysis showed that only multiparous women in the Foley alone group had lower rate of vaginal delivery within 24 hours (RR: 0.74, 95% CI [0.61–0.89], p = 0.002) along with a trend toward higher CD rates.Conclusion Adding oxytocin to FB at the time of preinduction cervical ripening does not reduce cesarean rates nor improve maternal or neonatal outcomes. Multiparous women who received FB alone seem to have lower rates of vaginal deliveries within 24 hours, but these results should be interpreted with caution.
Keywords: preinduction; oxytocin; Foley; cervical ripening; induction; labor; cesarean